Cell cycle-related shifts in subcellular localization of BCR: association with mitotic chromosomes and with heterochromatin. - Wetzler, M (1995)
The disruption of the BCR gene and its juxtaposition to and consequent activation of the ABL gene has been implicated as the critical molecular defect in Philadelphia chromosome-positive leukemias. The normal BCR protein is a multifunctional molecule with domains that suggest its participation in phosphokinase and GTP-binding pathways. Taken together with its localization to the cytoplasm of uncycled cells, it is therefore presumed to be involved in cytoplasmic signaling. By performing a double aphidicolin block for cell cycle synchronization, we currently demonstrate that the subcellular localization of BCR shifts from being largely cytoplasmic in interphase cells to being predominantly perichromosomal in mitosis. Furthermore, with the use of immunogold labeling and electron microscopy, association of BCR with DNA, in particular heterochromatin, can be demonstrated even in quiescent cells. Results were similar in cell lines of lymphoid or myeloid origin. These observations suggest a role for BCR in the phosphokinase interactions linked to condensed chromatin, a network previously implicated in cell cycle regulation.